PENGARUH KESADARAN WP, PEMAHAMAN PERPAJAKAN, SANKSI PAJAK DAN AKUNTABILITAS PELAYANAN PUBLIK PADA KEPATUHAN WAJIB PAJAK - Purwita Sari, Kadek Dita; Astika, Ida Bagus Putra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.12.TAHUN.2023DO - 10.24843/EEB.2023.v12.i12.p16, 2023)
The largest source of state revenue is taxes. Tax is an effort made by the government to realize its independence. The role of taxes as state revenue is very dominant, but it is still not optimal considering the number of non-compliant taxpayers. This study aims to empirically examine the effect of taxpayer awareness, level of understanding of taxation, tax sanctions and public service accountability on the compliance of motorized vehicle taxpayers registered at the Badung Samsat Office. Accidental Sampling was used as a sampling method and obtained as many as 100 samples of motor vehicle taxpayers. This study uses multiple linear regression analysis techniques. The results of this study indicate that taxpayer awareness, level of understanding of taxation, tax sanctions and public service accountability have a positive effect on motor vehicle taxpayer compliance at the Badung Samsat Office. It is hoped that the Badung Samsat Office can further increase information on the importance of paying motorized vehicle taxes through webinars or seminars as well as online platforms or direct practice with assistance such as short videos on motor vehicle taxes and sanctions given for late payments in order to gain knowledge of taxation early on.